Rural development in the digital age : exploring neo-productivist EU rural policy - Pelucha, Martin; Kasabov, Edward (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Rural Development in the Digital Age explores current theoretical and policy developments in EU rural policy during the 4.0 period. The authors examine inconsistencies in the design and implementation of EU rural development policy driven largely by intensifying neo-productivist pressures. The importance and novelty of the book lie in defining and critically examining the territorial impacts of neo-productivism as an ideology, a practice and a set of policy imperatives during the EU's 2014-2020 programming period. The authors argue that such a paradigm shift in EU rural policy may reduce its effectiveness and ability to meet its goals of balanced territorial development and cohesion. This book will be of interest to advanced students, researchers and policymakers in rural policy, regional studies, economic geography and EU policy"--
OCLC-licensed vendor bibliographic record.
Keywords: Rural development -- European Union countries; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Development / Economic Development; BUSINESS & ECONOMICS / Economics / General; European Union countries -- Rural conditions